(untitled) (Nigerian Journal of Technology, 2018)
The need for low-cost wastewater treatment alternatives especially in poor hinterlands, where synthetic coagulants or activated carbon may not be cheaply and readily available, necessitated this study. Moringa Oleifera (MO) kernel was investigated as coagulant in the purification of wastewater polluted with lead. The adsorption potential of MO was also investigated. MO with effective size of 0.14mm was used in the preparation of stock solutions with dosages of 500mg/l and 1000mg/l. Synthetic wastewater polluted with lead monoxide was prepared. The wastewater had an initial concentration of 0.216mg/l of lead. 2%, 4%, 6%, 8% and 10% of the stock solutions were added to the wastewater samples. The samples were subjected to jar test experiments. The research revealed that efficiency of lead removal increases with increase in the concentration of the MO coagulant. For one hour contact time, a maximum efficiency of 35.2% of lead removal was achieved when 10% of the stock solution (1000mg/l solution) was added. The fitting of the experimental data with the Langmuir and Freundlich adsorption isotherm models yielded R2 values of 0.784 and 0.906, respectively for the 1000mg/l dosage stock solution. Freundlich model described the lead (Pb) adsorption better than the Langmuir model. Chemisorption was suggested to be involved in lead (Pb) adsorption (adsorption intensity n<1). The utilization of the extraction method presented in this research proposes the combination of the MO coagulants with the inorganic coagulants. Key words: Investigation; Moringa Olifera; lead; purification; wastewater http://dx.doi.org/10.4314/njt.v38i1.30